1997
DOI: 10.1007/bf01142677
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative control by somatosensory evoked potentials in the treatment of cervical myeloradiculopathy. Results in 210 cases

Abstract: Somatosensory evoked potentials (SEPs) were used for continuous monitoring of 210 patients during anterior surgery for cervical myeloradiculopathy, to test how effectively they help avoid irreversible neurological damage during surgery. The pathologies differed in severity and were treated by diskectomy or by extended corporectomy using the Senegas technique. Intraoperative SEP changes were recorded in 84 patients (40%); in 13 (6.2%) of these, changes in SEP amplitude and latency were caused by mechanical stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…15,17,18,20,22 Six studies analyzed patients monitored with a unimodal technique; 11,15,16,18,19,22 five of which used SSEP, 11,15,18,19,22 and one of which used MEP 16 (Table 3). 11,1422 …”
Section: Resultsmentioning
confidence: 99%
“…15,17,18,20,22 Six studies analyzed patients monitored with a unimodal technique; 11,15,16,18,19,22 five of which used SSEP, 11,15,18,19,22 and one of which used MEP 16 (Table 3). 11,1422 …”
Section: Resultsmentioning
confidence: 99%
“…This indicates that SSEPs are affected by a lowering of the spinal cord perfusion pressure, as corroborated by other investigators. 8,26 It has been demonstrated that raising systemic blood pressure results in an improvement of SSEPs when such signal deterioration occurs in the setting of hypotension. 6 It has not escaped our attention that none of the patients who had reversible SSEP changes with hypotension, intervertebral disc space distraction, and patient/retractor positioning had a neurologic deficit ( Table 2).…”
Section: E109 Ssep Monitoring For Cervical Corpectomy • Khan Et Almentioning
confidence: 98%
“…For example, most studies have combined data from patients undergoing cervical spine corpectomy surgery with patients undergoing anterior cervical discectomy and fusion. 6,8 However, because of underlying pathophysiologic differences between cervical myelopathy and radiculopathy, these groups need to be studied separately. Also, since there are significant technical differences between cervical spine corpectomy and discectomy surgeries, the results of these surgical procedures should be interpreted in the appropriate context.…”
mentioning
confidence: 99%
“…Authors of studies examining the utility of EP monitoring as a diagnostic or therapeutic tool have used "clinically relevant neurological injury" as the outcome measure. Sebastian et al 19 described a series of 210 patients who underwent SSEP monitoring during anterior decompressive surgery for CSM. These authors found that significant changes occurred in 84 patients, with 44 patients showing improvement in monitoring, and 40 showing significant worsening or unstable responses.…”
Section: Scientific Foundationmentioning
confidence: 99%